ASAS MILITARY NECESSITY PADA KONFLIK BERSENJATA UNTUK MELINDUNGI PENDUDUK SIPIL - Nexel Yosua Sompotan; Lesza Leonardo Lombok; Marven Ajels Kasenda (Fakultas Hukum Universitas Ngurah Rai, 2025)
Military Necessity is a fundamental principle in international humanitarian law that permits military actions necessary to achieve legitimate military objectives, but must still limit harm to civilian populations and civilian infrastructure. This study aims to analyze the application of this principle in contemporary armed conflicts, focusing on efforts to protect civilians. The research examines the Geneva Conventions, Additional Protocols, and case studies of modern conflicts to understand the relationship between Military Necessity and the principle of proportionality, as well as the challenges that arise in its implementation, particularly in asymmetric conflicts where combatants and non-combatants are often blended. The findings suggest that while this principle is widely accepted, its application still frequently presents challenges that lead to violations of international humanitarian law. Therefore, recommendations to strengthen the implementation of this principle should be considered in order to enhance protection for civilians in armed conflicts